Sabu Raijua: Hydraulic Mission and Evaporation Threat - Suni, Yulius Patrisius Kau; Kini, Lodi Meda; Benge, Fabianus (CV. Gio Architect, 2024)
In Sabu Raijua, the more than 200-year-old hydraulic mission just began to demonstrate its dynamics in 2011. This study, which employs the literature review method and field survey, discusses the hydraulic mission and examines the challenges associated with evaporation for farm pond, also known as embung (in Indonesia), in Sabu Raijua. According to the data search findings, the government constructed large and small embungs in 230 locations between 2011 and 2018 with funding assistance from the district and the central governments. The presence of a large number ponds—nearly four times as many as kelurahans or villages—seems to be a blessing of aridity for this region. However, the mission still has to deal with socioeconomic issues like a petition against the construction of the Guriola reservoir, a series of droughts, and the threat of evaporation. All of Sabu Raijua's reservoirs had a loss of water of more than 50% in the fifth year of drought since 2015. Low rainfall is a contributing factor, although it is not the only one. According to the analysis of climate data, Sabu Raijua has evaporation risks from April through November, peaking in August, during both normal and below normal rainy periods.